Male and Female EFL Students’ Learning Style at Muhammadiyah University of Makassar - Baharu, Hijrah (ELT Worldwide: Journal of English Language Teaching, 2019)
This study is intended to answer the main research questions related to the students’ learning style preferences that used dominantly by male and female students at Muhammadiyah University of Makassar in 2017/2018 academic years. Their gender differences in communication affect the students’ learning style. There were 20 students involved as the participants of the study which were selected by using convenient sampling. The data were collected by using three instruments: observation, diaries and questionnaire. Then, the data were analyzed by using mixed methods both qualitatively and quantitatively. Qualitative data were obtained from observations and diaries while quantitative data were obtained from questionnaires. The procedures of data analysis consisted of data reduction, data display, and drawing conclusion or verification. The result of this study shows that the learning style that used dominantly by female students is kinesthetic learning style. Moreover, the data also showed that the male students tend to use auditory learning style. Whereas, in terms of individual and group learning style preference, there were no significant differences between male and female in working as a group and individual. In addition, there is an effect of gender difference in term of learning style because of the notions of male and female’s communication. The male students’ preferred auditory learning style because male students tended to enjoy and more active to learn by hearing music and short video as learning media. On the other hand, female students preferred kinesthetic learning style because they learn best by being involved physically in the classroom, such as learning by doing and learning by using games. These styles of learning are affected by the notions of gender differences in communication.